ANALISIS EKOLOGI ADMINISTRASI: DAMPAK PEMBANGUNAN BANDARA INTERNASIONAL JAWA BARAT (BIJB) KERTAJATI DI DESA PUTRIDALEM KECAMATAN JATITUJUH KABUPATEN MAJALENGKA - Bagus Tsany Fadillah Rochman; Chitra Meilina; Cindy Elik Fajriati; Dea Nur Amalia; Haris Subhan (Jurnal Inovasi Penelitian, 2021)
Development in general is a process of continuous change towards a better condition based on certain rules. In a development there must be an impact produced, all of these impacts will result in changes that occur in society. Likewise, the construction of Kertajati West Java International Airport (BIJB) will certainly have positive and negative impacts on various aspects in Majalengka Regency, especially in Putridalem Village, Jatit Tujuh Subdistrict. The purpose of this research is to know the impact of the construction of the airport on the ecological aspects of administration in Putridalem Village. This type of research is descriptive using a qualitative approach. Data collection techniques through interviews and documentation. The types of data used are primary data and secondary data. The conclusion from the study shows that the construction of West Java International Airport (BIJB) Kertajati in terms of several aspects contained in administrative ecological factors has quite a lot of positive impacts on Putridalem Village